Monetary Flexibility, Exchange Rate Regimes - Gassem ,Mohammed Fouad; Zemri Bouazza ,Elamine (جامعة الوادي University of Eloued, 2025)
This study examines the impact of exchange rate regimes on economic growth in selected MENA countries from 1980 to 2023 using panel data and a Panel VAR framework. Employing unit root tests, Pedroni cointegration, Granger causality, variance decomposition, and impulse response functions, it finds no long-run cointegration between regimes and growth. However, short-term dynamics reveal that fixed regimes rely heavily on exports and GDP, while intermediate regimes display more self-contained stability. The results highlight that no single regime is optimal, emphasizing the need for context-specific exchange rate strategies tailored to each country’s structural and macroeconomic conditions.
Monetary Flexibility, Exchange Rate Regimes, and Economic Performance in the Middle East and North Africa
مقال
Keywords: Exchange Rate Regimes; Economic Growth; MENA Region; Panel VAR